Psychometric evaluation of the chinese version of transgender congruence scale - Lvfen Gao; Xu Zhang; Huiyi Li; Chuying Lu; Jinhui Li; Qian Tao (BMC Psychology)
Abstract Background In China, research on the mental health of transgender populations is increasingly prevalent; however, there is a lack of localized psychological measurement tools that align with the characteristics of this population. The Transgender Congruence Scale (TCS) is widely used internationally. This study aims to assess the reliability, validity, and psychometric characteristics of the Chinese version of the TCS among the Chinese transgender sample. Methods A total of 264 participants with a mean age of 24.88 (SD = 5.91) were recruited from October 2023 to January 2024. They completed the Chinese version of the TCS, the Satisfaction with Life Scale (SWLS), and the Depression, Anxiety, and Stress Scale-21 (DASS-21). Confirmatory factor analysis of the TCS was performed using IBM SPSS Amos 28 software to assess the construct validity. Reliability, convergent validity, and measurement invariance analysis were also evaluated. Results The reliability coefficients of the revised 9-item TCS were satisfactory (Cronbach’s α = 0.85, McDonald’s ω = 0.87). The two-factor model of the instrument was supported (χ 2 (26) = 52.525, p = 0.002, CFI = 0.979, TLI = 0.971, SRMR = 0.052, RMSEA = 0.062 [90% CI = 0.037, 0.086]). The TCS scores significantly correlated with life satisfaction (r = 0.486, p < 0.001), stress (r = -0.182, p < 0.01), depression (r = -0.176, p < 0.01), and anxiety (r = -0.176, p < 0.01). The measurement validity of the TCS is good across different gender identity groups. Conclusions These findings suggested that the TCS can serve as a short yet effective tool for assessing the congruence between external appearance and internal self among TGD individuals in clinical or research settings.